Systematic Job Search and Unemployment - Salop, S. C. (Review of Economic Studies, 1973)
Journal Article Systematic Job Search and Unemployment Get access S. C. Salop S. C. Salop Board of Governors of the Federal Reserve Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 40, Issue 2, April 1973, Pages 191–201, https://doi.org/10.2307/2296647 Published: 01 April 1973